Therapeutic Management of Theileriosis in Holstein friesian Cows - Gagandeep Singh; Deepak Sumbria; Nischal Dutta; Rabjot Kour; Anand Prakash; Kapil Gupta; Vikrant Sudan (The Indian Veterinary Journal, 2025)
One of the most important tick borne haemoprotozan disease in livestock is Theileriosis. This disease causes heavy morbidity and mortality in cattle and result in financial loss to the dairy farmer. Theileriaannulata is one of the main protozoan parasites responsible for Theileriosis in India. Current manuscript report two cases of Theileriosis in RampuraPhul along with its haematological finding and therapeutic management. Convention method of parasite screening revealed comma shape of parasite in red blood cell and Koch’s blue body in lymphocyte. The infected animal was treated with Butalex @2.5 mg/kg BW plus supportive treatment and eventually animal recovered from infection